Pengaruh Penghargaan Diri (Self-Esteem), Dukungan Sosial, dan Sosial Budaya Terhadap Kesejahteraan Subjektif Pekerja Migran Perempuan di Kabupaten Gianyar - Puspita, Luh Putu Yuni; Suwena , Kadek Rai (Universitas Pendidikan Ganesha, 2025)
High-income work opportunities abroad are a trend for most people, including women in Gianyar Regency in an effort to improve the family economy and life satisfaction. This study aims to analyze the influence of self-esteem, social support, and socio-culture on the subjective well-being of female migrant workers in Gianyar Regency. This study uses a quantitative approach with multiple linear regression methods. The research sample amounted to 117 respondents selected by purposive sampling technique. The results showed that self-esteem, social support, and socio-culture had a positive and significant effect on the subjective well-being of female migrant workers. The self-esteem variable has the most dominant influence, followed by social support and socio-culture. Thus, increasing self-esteem which reflects self-confidence and appreciation of one's abilities as well as social support which includes emotional support from the surrounding environment can be an effective strategy in improving the subjective well-being of female migrant workers.